Survey of indigenous firms: A snapshot of wages, prices and financing in the indigenous business sector in Canada - Calista Cheung; James Fudurich; Janki Shah; Farrukh Farrukh Suvankulov (Bank of Canada, 2024)
Attempts to measure and track the Indigenous economy in Canada are limited by data availability and quality. Also, little is known about the business environment on reserves. Filling these information gaps is important to ensure that policy-makers and Indigenous leaders can make well-informed decisions that benefit the long-term prosperity of Indigenous communities. To help narrow these knowledge gaps, the Bank of Canada partnered with the Canadian Council for Aboriginal Business and Global Affairs Canada to conduct a large-scale, national survey of Indigenous-owned firms between May and September 2021. This paper reports findings from the survey results, including Indigenous-owned firms' main sources of financing and their expectations about wages, prices and inflation. These results are compared with those from other Canadian business surveys such as the Bank's quarterly Business Outlook Survey (BOS) to better understand the unique conditions and challenges Indigenous businessesface. Overall, we find that, compared with the average small business in Canada, Indigenous firms were significantly less likely to use financial institutions as main sources of financing. Indigenous businesses also had stronger inflation expectations and weaker wage-growth expectations, on average, than non-Indigenous firms in Canada, based on results from the BOS during the same time frame. The relatively high inflation expectations partly reflect the large share of Indigenous firms located in rural areas compared with the total business population in Canada. Indigenous firms in rural locations tended to expect higher inflation and higher price increases than their counterparts in urban areas.
Keywords: C83; D0; J15; G38; 330; Firm dynamics